Download presentation
Presentation is loading. Please wait.
Published byJustin Anthony Modified over 9 years ago
1
7.1 – Operations on Functions
2
OperationDefinition
3
Sum
4
OperationDefinition Sum(f + g)(x)
5
OperationDefinition Sum(f + g)(x) = f(x) + g(x)
6
OperationDefinition Sum(f + g)(x) = f(x) + g(x) Difference
7
OperationDefinition Sum(f + g)(x) = f(x) + g(x) Difference(f – g)(x) =
8
OperationDefinition Sum(f + g)(x) = f(x) + g(x) Difference(f – g)(x) = f(x) – g(x)
9
OperationDefinition Sum(f + g)(x) = f(x) + g(x) Difference(f – g)(x) = f(x) – g(x) Product
10
OperationDefinition Sum(f + g)(x) = f(x) + g(x) Difference(f – g)(x) = f(x) – g(x) Product(f · g)(x) =
11
OperationDefinition Sum(f + g)(x) = f(x) + g(x) Difference(f – g)(x) = f(x) – g(x) Product(f · g)(x) = f(x) · g(x)
12
OperationDefinition Sum(f + g)(x) = f(x) + g(x) Difference(f – g)(x) = f(x) – g(x) Product(f · g)(x) = f(x) · g(x) Quotient f (x) = g
13
OperationDefinition Sum(f + g)(x) = f(x) + g(x) Difference(f – g)(x) = f(x) – g(x) Product(f · g)(x) = f(x) · g(x) Quotient f (x) = f(x) g g(x)
14
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9
15
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x)
16
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x)
17
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x)
18
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x) = (2x – 3)
19
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x) = (2x – 3)
20
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x) = (2x – 3) + (4x + 9)
21
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x) = (2x – 3) + (4x + 9) = 6x + 6
22
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x) = (2x – 3) + (4x + 9) = 6x – 6 (f – g)(x)
23
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x) = (2x – 3) + (4x + 9) = 6x – 6 (f – g)(x) = f(x) – g(x)
24
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x) = (2x – 3) + (4x + 9) = 6x – 6 (f – g)(x) = f(x) – g(x)
25
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x) = (2x – 3) + (4x + 9) = 6x – 6 (f – g)(x) = f(x) – g(x) = (2x – 3)
26
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x) = (2x – 3) + (4x + 9) = 6x – 6 (f – g)(x) = f(x) – g(x) = (2x – 3)
27
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x) = (2x – 3) + (4x + 9) = 6x – 6 (f – g)(x) = f(x) – g(x) = (2x – 3) – (4x + 9)
28
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x) = (2x – 3) + (4x + 9) = 6x – 6 (f – g)(x) = f(x) – g(x) = (2x – 3) – (4x + 9)
29
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x) = (2x – 3) + (4x + 9) = 6x – 6 (f – g)(x) = f(x) – g(x) = (2x – 3) – (4x + 9) = 2x – 3 – 4x
30
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x) = (2x – 3) + (4x + 9) = 6x – 6 (f – g)(x) = f(x) – g(x) = (2x – 3) – (4x + 9) = 2x – 3 – 4x – 9
31
Ex. 1 Find (f + g)(x), (f – g)(x), (f · g)(x), & f (x)for f(x) g and g(x) if f(x) = 2x – 3 and g(x) = 4x + 9 (f + g)(x) = f(x) + g(x) = (2x – 3) + (4x + 9) = 6x – 6 (f – g)(x) = f(x) – g(x) = (2x – 3) – (4x + 9) = 2x – 3 – 4x – 9 = -2x – 12
32
(f · g)(x)
33
(f · g)(x) = f(x) · g(x)
35
= (2x – 3)
36
(f · g)(x) = f(x) · g(x) = (2x – 3)
37
(f · g)(x) = f(x) · g(x) = (2x – 3)(4x + 9)
38
(f · g)(x) = f(x) · g(x) = (2x – 3)(4x + 9) = 8x 2 + 18x – 12x – 27
39
(f · g)(x) = f(x) · g(x) = (2x – 3)(4x + 9) = 8x 2 + 18x – 12x – 27 = 8x 2 + 6x – 27
40
(f · g)(x) = f(x) · g(x) = (2x – 3)(4x + 9) = 8x 2 + 18x – 12x – 27 = 8x 2 + 6x – 27 f (x) g
41
(f · g)(x) = f(x) · g(x) = (2x – 3)(4x + 9) = 8x 2 + 18x – 12x – 27 = 8x 2 + 6x – 27 f (x) = f(x) g g(x)
42
(f · g)(x) = f(x) · g(x) = (2x – 3)(4x + 9) = 8x 2 + 18x – 12x – 27 = 8x 2 + 6x – 27 f (x) = f(x) g g(x) = 2x – 3 4x + 9
43
(f · g)(x) = f(x) · g(x) = (2x – 3)(4x + 9) = 8x 2 + 18x – 12x – 27 = 8x 2 + 6x – 27 f (x) = f(x) g g(x) = 2x – 3 4x + 9 *Factor & Simplify if possible!
44
Composite Function
45
- taking the function
46
Composite Function - taking the function of a function
47
Composite Function - taking the function of a function [f °g(x)]
48
Composite Function - taking the function of a function [f °g(x)] = f[g(x)]
49
Composite Function - taking the function of a function [f °g(x)] = f[g(x)] Ex. 2 Find [f °g(x)] and [g°f(x)] for the functions f(x) = x + 3 and g(x) = x 2 + x – 1.
50
Composite Function - taking the function of a function [f °g(x)] = f[g(x)] Ex. 2 Find [f °g(x)] and [g°f(x)] for the functions f(x) = x + 3 and g(x) = x 2 + x – 1. [f °g(x)] = f[g(x)]
51
Composite Function - taking the function of a function [f °g(x)] = f[g(x)] Ex. 2 Find [f °g(x)] and [g°f(x)] for the functions f(x) = x + 3 and g(x) = x 2 + x – 1. [f °g(x)] = f[g(x)]
52
Composite Function - taking the function of a function [f °g(x)] = f[g(x)] Ex. 2 Find [f °g(x)] and [g°f(x)] for the functions f(x) = x + 3 and g(x) = x 2 + x – 1. [f °g(x)] = f[g(x)] = f[x 2 + x – 1]
53
Composite Function - taking the function of a function [f °g(x)] = f[g(x)] Ex. 2 Find [f °g(x)] and [g°f(x)] for the functions f(x) = x + 3 and g(x) = x 2 + x – 1. [f °g(x)] = f[g(x)] = f[x 2 + x – 1]
54
Composite Function - taking the function of a function [f °g(x)] = f[g(x)] Ex. 2 Find [f °g(x)] and [g°f(x)] for the functions f(x) = x + 3 and g(x) = x 2 + x – 1. [f °g(x)] = f[g(x)] = f[x 2 + x – 1]
55
Composite Function - taking the function of a function [f °g(x)] = f[g(x)] Ex. 2 Find [f °g(x)] and [g°f(x)] for the functions f(x) = x + 3 and g(x) = x 2 + x – 1. [f °g(x)] = f[g(x)] = f(x 2 + x – 1) = (x 2 + x – 1) + 3
56
Composite Function - taking the function of a function [f °g(x)] = f[g(x)] Ex. 2 Find [f °g(x)] and [g°f(x)] for the functions f(x) = x + 3 and g(x) = x 2 + x – 1. [f °g(x)] = f[g(x)] = f(x 2 + x – 1) = (x 2 + x – 1) + 3 = x 2 + x + 2
57
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)]
58
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)]
59
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)]
60
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)]
61
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3)
62
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3)
63
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3)
64
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2
65
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2
66
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2 + (x + 3)
67
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2 + (x + 3)
68
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2 + (x + 3) – 1
69
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2 + (x + 3) – 1 = (x + 3)(x + 3) + (x + 3) – 1
70
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2 + (x + 3) – 1 = (x + 3)(x + 3) + (x + 3) – 1 = x 2 + 6x + 9 + x + 3 – 1
71
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2 + (x + 3) – 1 = (x + 3)(x + 3) + (x + 3) – 1 = x 2 + 6x + 9 + x + 3 – 1 = x 2 + 7x + 11
72
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2 + (x + 3) – 1 = (x + 3)(x + 3) + (x + 3) – 1 = x 2 + 6x + 9 + x + 3 – 1 = x 2 + 7x + 11 Ex. 3 If f(x) = 4x and g(x) = 2x – 1, find g[f(5)].
73
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2 + (x + 3) – 1 = (x + 3)(x + 3) + (x + 3) – 1 = x 2 + 6x + 9 + x + 3 – 1 = x 2 + 7x + 11 Ex. 3 If f(x) = 4x and g(x) = 2x – 1, find g[f(5)]. g[f(5)] =
74
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2 + (x + 3) – 1 = (x + 3)(x + 3) + (x + 3) – 1 = x 2 + 6x + 9 + x + 3 – 1 = x 2 + 7x + 11 Ex. 3 If f(x) = 4x and g(x) = 2x – 1, find g[f(5)]. g[f(5)] =
75
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2 + (x + 3) – 1 = (x + 3)(x + 3) + (x + 3) – 1 = x 2 + 6x + 9 + x + 3 – 1 = x 2 + 7x + 11 Ex. 3 If f(x) = 4x and g(x) = 2x – 1, find g[f(5)]. g[f(5)] =
76
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2 + (x + 3) – 1 = (x + 3)(x + 3) + (x + 3) – 1 = x 2 + 6x + 9 + x + 3 – 1 = x 2 + 7x + 11 Ex. 3 If f(x) = 4x and g(x) = 2x – 1, find g[f(5)]. g[f(5)] = g[4(5)]
77
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2 + (x + 3) – 1 = (x + 3)(x + 3) + (x + 3) – 1 = x 2 + 6x + 9 + x + 3 – 1 = x 2 + 7x + 11 Ex. 3 If f(x) = 4x and g(x) = 2x – 1, find g[f(5)]. g[f(5)] = g[4(5)] = g(20)
78
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2 + (x + 3) – 1 = (x + 3)(x + 3) + (x + 3) – 1 = x 2 + 6x + 9 + x + 3 – 1 = x 2 + 7x + 11 Ex. 3 If f(x) = 4x and g(x) = 2x – 1, find g[f(5)]. g[f(5)] = g[4(5)] = g(20)
79
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2 + (x + 3) – 1 = (x + 3)(x + 3) + (x + 3) – 1 = x 2 + 6x + 9 + x + 3 – 1 = x 2 + 7x + 11 Ex. 3 If f(x) = 4x and g(x) = 2x – 1, find g[f(5)]. g[f(5)] = g[4(5)] = g(20) = 2(20) – 1
80
f(x) = x + 3 and g(x) = x 2 + x – 1 [g°f(x)] = g[f(x)] = g(x + 3) = (x + 3) 2 + (x + 3) – 1 = (x + 3)(x + 3) + (x + 3) – 1 = x 2 + 6x + 9 + x + 3 – 1 = x 2 + 7x + 11 Ex. 3 If f(x) = 4x and g(x) = 2x – 1, find g[f(5)]. g[f(5)] = g[4(5)] = g(20) = 2(20) – 1 = 39
81
7.3 – Square Root Functions & Inequalities
82
Ex. 1 Identify the domain & range of each function. a. y = √ x + 4
83
Ex. 1 Identify the domain & range of each function. a. y = √ x + 4 x + 4 = 0
84
Ex. 1 Identify the domain & range of each function. a. y = √ x + 4 x + 4 = 0 x = -4
85
Ex. 1 Identify the domain & range of each function. a. y = √ x + 4 x + 4 = 0 x = -4 Domain: { x | x > -4}
86
Ex. 1 Identify the domain & range of each function. a. y = √ x + 4 x + 4 = 0 x = -4 Domain: { x | x > -4} y = √ x + 4
87
Ex. 1 Identify the domain & range of each function. a. y = √ x + 4 x + 4 = 0 x = -4 Domain: { x | x > -4} y = √ x + 4
88
Ex. 1 Identify the domain & range of each function. a. y = √ x + 4 x + 4 = 0 x = -4 Domain: { x | x > -4} y = √ x + 4 y = √ -4+ 4
89
Ex. 1 Identify the domain & range of each function. a. y = √ x + 4 x + 4 = 0 x = -4 Domain: { x | x > -4} y = √ x + 4 y = √ -4+ 4 y = 0
90
Ex. 1 Identify the domain & range of each function. a. y = √ x + 4 x + 4 = 0 x = -4 Domain: { x | x > -4} y = √ x + 4 y = √ -4+ 4 y = 0 Range: { y | y > 0}
91
Ex. 2 Graph each function. State the domain & range. a. y = √ x + 4 Domain: { x | x > -4}, Range: { y | y > 0} Graph: Y= 2 nd, x 2 x + 4) Zoom:6 2 nd Graph Plot at least 3 points of curve (x & y ints. & one other pt.)
92
xy -40 -31 02
93
Ex. 3 Graph each inequality a. y <√ x + 4 Graph: Y= Cursor left to \ Press “Enter” until (If > make it ) 2 nd, x 2 x + 4) Zoom:6 2 nd Graph Plot at least 3 points of curve (x & y ints. & one other pt.)
94
xy -40 -31 02
Similar presentations
© 2024 SlidePlayer.com. Inc.
All rights reserved.